Estudo da toxicidade de diferentes doses do Diuron (3-(3,4 -dichlorophenyl)-1,1-dimethylurea) no epitélio da bexiga de ratos wistas machos por microscopia eletrônica de varredura - Cardoso, Ana Paula Ferragut [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Diuron (3-(3,4-Dichlorophenyl)-1,1-dimethylurea) is a substituted urea herbicide widely used on agricultural crops such as soy, cotton and sugar cane. In a previous long-term study this herbicide exerted carcinogenic activity on the urinary bladder and renal pelvis mucosa of Wistar rats and breast of mice. Also, it was shown to be carcinogenic to the mice skin in a initiation-promotion assay. In 1997, the northamerican EPA evaluated Diuron as a “known/likely” carcinogen for humans (USEPA, 2004). In a previous study developed at this laboratory, male Wistar rats treated with Diuron 2500 ppm during 20 weeks presented increased indices of cell proliferation and incidences of simple urothelial hyperplasia (HS) in the urinary bladder. Under scanning electron microscopy (SEM) severe urothelial necrosis and hyperplasia were observed. However, in that study the urinary bladders of animals exposed to lower doses of Diuron were not examined under SEM. Therefore, the possible dose-response influence of Diuron on the urothelium under SEM is not known. The present study aimed to analyze under SEM the urinary bladder of male Wistar rats exposed to 125 ppm, 500 ppm and 2500 ppm doses of Diuron through diet during 20 weeks and to compare to the previous histological findings in the same material. Under SEM, 125 ppm and 2500 ppm groups presented significantly (p<0,05) increased incidences of simple hyperplasia, i.e., 7/10 and 8/10 respectively, compared to control group and the 500 ppm group The sensitivity of SEM was higher since it detected a 45% incidence of hyperplasiaswhile the histological analysis found only 27%. Considering SEM as the gold-standard, histology showed a 44% sensitivity, 86.4% specificity, a positive predictive value of 72,7% and negative predictive value of 65,5% and accuracy of 67,5%. Scanning Electron Microscopy...(Complete abstract click electronic access below)

O Diuron (3-(3,4-Dichlorophenyl)-1,1-dimethylurea) é um herbicida derivado da uréia, muito utilizado no Brasil para controlar plantas daninhas nas culturas de soja, algodão e cana de açúcar, entre outras. Evidências experimentais indicam que o Diuron é cancerígeno para roedores; induz tumores na pele e mama de camundongos, e na bexiga e pelve renal de ratos, quando administrado pela ração em concentrações elevadas. O Diuron foi classificado pela agência ambiental norte-americana (EPA) como “provável cancerígeno para a espécie humana”. Em um estudo prévio desenvolvido por nosso grupo, ratos Wistar machos tratados com Diuron 2500 ppm durante 20 semanas apresentaram aumento dos índices de proliferação celular e da incidência de hiperplasia urotelial simples (HS) na bexiga. À microscopia eletrônica de varredura (MEV) foram observados focos de necrose grave e hiperplasia do urotélio vesical dos animais expostos ao herbicida. Porém, nesse estudo não foram avaliados possíveis alterações uroteliais nas bexigas de animais expostos a concentrações menores de Diuron, de modo que não se sabe se há efeito doseresposta do Diuron sobre o urotélio. O objetivo deste trabalho foi estudar por MEV a ação do Diuron sobre o epitélio da bexiga de ratos Wistar machos expostos as doses de 125, 500 e 2500 ppm durante 20 semanas e verificar a existência de eventual dose-resposta nos fenômenos de citotoxicidade e regeneração celular e ainda, comparar os achados da MEV com os histológicos verificados previamente nas mesma bexigas. Os grupos 125ppm e 2500ppm de Diuron apresentaram incidências significativamente maiores (p<0,05) de lesões na mucosa, i.e, 7/10 e 8/10 respectivamente, comparados ao grupo controle e ao grupo 500ppm. Ao compararmos ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Diuron - Efeito fisiológico; Toxicidade - Teses; Microscopia eletrônica de varredura; Scanning Electron Microscopy